Pembrolizumab for recurrent/metastatic head and neck squamous cell carcinoma in an Asian population. Issue 52 (December 2017) - Chen, Wen-Chun; Chu, Pen-Yuan; Lee, Yu-Ting; Lu, Wen-Bin; Liu, Chun-Yu; Chang, Peter Mu-Hsin; Yang, Muh-Hwa
Abstract : Abstract: Head and neck squamous cell carcinoma (HNSCC) has a high prevalence and is a major cause of cancer deaths in Taiwan. However, there is still no effective salvage therapy that prolongs the life expectancy of patients with recurrent/metastatic (R/M) HNSCC. Immune checkpoint therapy that targets the programmed cell death protein 1 (PD-1) may provide clinical benefit for these patients. We analyzed 22 R/M HNSCC patients who received pembrolizumab, a monoclonal antibody against PD-1, as salvage therapy. Intravenous pembrolizumab was given at a fixed dosage of 100 or 200 mg every 3 weeks. Three patients also received local palliative radiotherapy, but no patients received chemotherapy or targeted drugs. Seventeen patients (77.3%) received at least 3 cycles of pembrolizumab. Based on Response Evaluation Criteria in Solid Tumors criteria (ver. 1.1), 2 patients (9.1%) had complete response, 5 (22.7%) had partial response, and 6 (27.3%) had stable disease, corresponding to a disease control rate of 59.1%. Four patients had confirmed disease progression, 2 of whom had continuous progression over the target lesion after shrinkage of other metastases. One patient developed immune-related pneumonitis that resolved quickly after steroid treatment. Another patient developed itchy skin rashes immediately after administration of pembrolizumab, and this was controlled by an antihistamine. There were no other severe adverse effects. Pembrolizumab is beneficial and well-tolerated for some patients with refractory R/M HNSCC. However, it is important to identify biomarkers to identify the most responsive patients when designing future trials.